Peran Komisi Pemilihan Umum Dalam Pilkada Kabupaten Solok Sumatera Barat Perspektif Fiqh Siyāsah - Dian Aditiya Perdana; Fauziah Febrinaldi (Yayasan Lembaga Studi Makwa, 2022)
During the stages of the regional head election (PILKADA) held by the Solok Regency KPU, namely the election of the Regent and Deputy Regent, there were several election disputes that were faced by the Solok Regency KPU, namely the nomination process dispute to the Bawaslu and PTTUN Medan, as well as the result dispute to the Constitutional Court (MK). Of the several disputes, one pair of candidates submitted an application, only one application was granted and two applications were rejected. The two disputes that were rejected were the candidacy disputes submitted to Bawaslu by the candidate pair Iriadi and Agus Syahdeman. Henceforth, the application submitted by the pair of pairs Nofi Chandra and Yulfadri to the Constitutional Court with the decision of Amar Rejecting the Petitioner's Application in its entirety. Based on the results of the study, the role of the Solok Regency KPU in resolving disputes over the election process for the Regent and Deputy Regent of Solok in 2020, the Solok Regency KPU has played as much as possible in accordance with the authority granted by laws and regulations, namely by preparing all the disputed answers and rebuttals, preparing the tools evidence, prepare witnesses and other documentation. In the view of siyasa fiqh, the Solok Regency KPU has received answers or materials in the trial. The dispute is resolved by the Qadha institution (Court) which is the institution tasked with resolving cases of disputes and their duties.